Pengaruh Penerapan Gaya Mengajar Komando Terhadap Kemampuan Passing Bawah Dalam Permainan Bola Voli Pada Siswa SMA Negeri 1 Tondano - Tira Faustina Batseran; Eduard E. Kumenap; Djoni Sunkudon (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
This study aims to analyze the impact of the implementation of the command teaching style on the ability of underhand passing in volleyball in students of SMA Negeri 1 Tondano. The main focus of this study is to compare the average score of underhand passing skills between students who receive teaching with the command style and those who do not receive special treatment. This study used an experimental design with a population of 120 grade 12 students at SMA Negeri 1 Tondano, and a sample of 20 students selected randomly. The sample was then divided into two groups, namely group A (experimental group) consisting of 10 students, and group B (control group) which also consisted of 10 students, with the division using a simple random sampling technique. The instrument used to measure underhand passing skills was the "Underhand passing skills test in volleyball." The results of the statistical test with the t test showed a t-count value of 3.81, while the t-table value at a significance level of 0.05 and 18 degrees of freedom was 2.101. Because t count is greater than t table (3.81 > 2.101), it can be concluded that the application of the command teaching style has a significant effect on underhand passing skills in volleyball games for students at SMA Negeri 1 Tondano.